PENDEKATAN HUMANISTIK DALAM PEMBELAJARAN BAHASA ARAB DI MTS. WALISONGO PURWOSARI PASURUAN - Nurrokhmatulloh; Evi Ning Muthoharoh; Ishfatul Millah (Journal Multicultural of Islamic Education, 2023)
Arabic language learning at Madrasah Tsanawiyah (MTS) Walisongo adopts humanism as a learning approach which has the main focus on developing students' human aspects. This approach emphasizes the importance of understanding and valuing students' roles in the learning process, as well as encouraging their personal development. In this approach, teachers at MTS Walisongo act as facilitators who help students to be actively involved in learning. They encourage open discussion, problem solving, and give students responsibility to take the initiative in learning Arabic. This aims to help students feel more ownership of their own learning. Apart from that, the humanistic approach in learning Arabic at MTS Walisongo also respects the uniqueness of each student. Teachers try to understand students' individual needs, interests and talents, so that learning can be adjusted to their level of ability and interest. This aims to create an environment that supports students' holistic personal development. This research aims to examine the implementation of a humanistic approach in learning Arabic at MTS Walisongo and its impact on students' personal abilities. By understanding this approach in more depth, it is hoped that it can provide valuable insight in improving the quality of Arabic language learning at MTS Walisongo and other similar institutions.